2009
DOI: 10.1162/jocn.2009.21110
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal Emotional Attention: Emotional Voices Modulate Early Stages of Visual Processing

Abstract: Emotional attention, the boosting of the processing of emotionally relevant stimuli, has, up to now, mainly been investigated within a sensory modality, for instance, by using emotional pictures to modulate visual attention. In real-life environments, however, humans typically encounter simultaneous input to several different senses, such as vision and audition. As multiple signals entering different channels might originate from a common, emotionally relevant source, the prioritization of emotional stimuli sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 53 publications
(85 reference statements)
8
57
1
Order By: Relevance
“…In fact, vocal emotions can serve a critical role in directing visual attention to emotionally relevant NOT THE FINAL VERSION events in the environment such as faces (Brosch, Grandjean, Sander, & Scherer, 2008;Paulmann, Titone, & Pell, 2012;. In terms of composition, vocal emotion expressions are characterized by ongoing changes in several acoustic parameters that are meaningful to listeners in combination-principally, these involve differences in pitch, loudness, rhythm, and voice quality (Banse & Scherer, 1996;Juslin & Laukka, 2003).…”
Section: Non-linguistic Vocalizations Versus Speech-embedded Emotionsmentioning
confidence: 99%
“…In fact, vocal emotions can serve a critical role in directing visual attention to emotionally relevant NOT THE FINAL VERSION events in the environment such as faces (Brosch, Grandjean, Sander, & Scherer, 2008;Paulmann, Titone, & Pell, 2012;. In terms of composition, vocal emotion expressions are characterized by ongoing changes in several acoustic parameters that are meaningful to listeners in combination-principally, these involve differences in pitch, loudness, rhythm, and voice quality (Banse & Scherer, 1996;Juslin & Laukka, 2003).…”
Section: Non-linguistic Vocalizations Versus Speech-embedded Emotionsmentioning
confidence: 99%
“…It is possible that at the early stage human brains are sensitive to general information of emotional prosody, rather than specific emotional category information. Previous oddball studies on emotional prosody usually interpret MMNs elicited by emotional deviants as an index of sensitivity to difference in emotional categories (Goydke et al 2004;Schirmer et al 2005), due to the evolutionary significance and the processing priority of emotional information (Brosch et al 2008(Brosch et al , 2009). Other than category processing view, our results revealed the simultaneous change detection in emotional category and physical properties, supporting the idea of early general information of emotional prosody.…”
Section: Early Stagementioning
confidence: 99%
“…The interaural level differences (ILDs) of the left and right channels were adjusted to create sounds that were approximately spatially matched to the locations of the visual targets, as this offers a closer resemblance to real-world environments (where correlated auditory and visual information often arise from a single spatial location (c.f., Brosch et al 2009)), compared to simple dichotic presentation. A preliminary experiment was run with three participants to determine the ILDs which best matched the locations of the visual targets, following a similar procedure to Meienbrock, Naumer, Doehrmann, Singer, & Muckli (2007).…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
“…For example, it has been shown that emotional pictures can improve categorization of auditory cues (Tartar, de Almeida, McIntosh, Rosselli, & Nash, 2012), and that emotional pictures, compared to neutral pictures, can bias attention towards non-emotional tactile and auditory targets (Van Damme, Gallace, Spence, Crombez, & Moseley, 2009). In particular, facilitated processing of visual targets has been reported following presentation of spatially uninformative cues conveying negative (Brosch, Grandjean, Sander and Scherer, 2008a) and positive prosody (Brosch, Grandjean, Sander, & Scherer, 2008b), and this type of crossmodal exogenous spatial cueing by emotional stimuli is thought to occur at a relatively early (i.e., perceptual) stage of processing, as revealed by event-related potentials (Brosch, Grandjean, Sander, & Scherer, 2009).…”
Section: Introductionmentioning
confidence: 99%